Government Health Expenditure and Policy for Public Health Outcomes: A Systematic Literature Review (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: The level of good governance, the efficiency of the healthcare system, and socioeconomic vulnerabilities all affect public health outcomes. Despite potential gains in terms of health outcomes, public healthcare investment has been extremely low in low-income countries. By improving the consolidation of healthcare system performance, this study helps the government and policymakers improve the quality of life in developing countries.MATERIALS AND METHODS: This study aims to assess the government health expenditure and policy for public health outcomes. The research is based on a review of empirical studies and reports. The PubMed search engine was used to locate research publications on government health expenditure and policy for public health outcomes. The PubMed Open Database was applied to find the publications using the keywords “health expenditure” and “health policy”. All papers that were published from January 1, 2013, to January 31, 2024, were checked for the study. 121 research papers were discovered during the initial inquiry; five duplicate articles were eliminated, and 84 were irrelevant to the study. Finally, 25 research papers and reports were selected for evaluation with the study titled “ Government Health Expenditure and Policy for Public Health Outcomes: A Systematic Literature Review”. RESULTS: Raising the nation’s social health insurance (SHI) coverage does not guarantee universal health care (UHC) or improved financial security. Extremely few people in poverty have health insurance and attempts to give them coverage through exemptions and waivers have not had the intended effect. To prevent families from being ruined due to family health problems, an innovative insurance plan needs to be created. Supply-side strategies, or health infrastructure, are needed to expand access to high-quality medical treatment.CONCLUSIONS: The quality of life in developing nations is directly improved by the consolidation of healthcare system performance, suggesting that policymakers should step in and offer financial and political help through a variety of policy options. Curative and preventive care are provided by health systems, which can greatly enhance people’s health. Developing a robust health finance system has been a primary objective for numerous countries worldwide, as increased public spending on healthcare leads to better health outcomes and more effective healthcare services. Financial limitations are one of the largest barriers to obtaining high-quality healthcare. A national health insurance program increased public financing for healthcare, and the construction of community-based clinics in rural areas could all contribute to the nation’s transition to universal health care. Policymakers ought to pay greater attention to the quality of care since it significantly affects the amount of money that patients must pay out-of-pocket. Governments must develop new internal financing sources and devise strategies to refocus on health promotion and prevention.